2018
DOI: 10.3847/1538-4357/aadb9f
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of Incompressible MHD Modes in Magnetic Cylinder with Twisted Magnetic Field and Flow

Abstract: In this work, we studied MHD modes in a magnetically twisted flux tube with a twisted flow that is embedded in the uniform magnetic field. We consider when the azimuthal magnetic field and velocity are linear functions of radius (case i) and also more generally when they are arbitrary functions of radius (case ii). Under these assumptions, we obtain the dispersion equation in the incompressible limit. This solution can also be used to describe the MHD perturbations in plasma pinches and vortices. The dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Hence, it looks like a viable assumption that the plasma flows along the magnetic field lines. In accordance with this, we now make the same assumption as in Cheremnykh et al (2018) and Bahari (2018), namely that the velocity is parallel to the magnetic field, U B. This assumption implies that…”
Section: Problem Formulation and Unperturbed Statementioning
confidence: 97%
“…Hence, it looks like a viable assumption that the plasma flows along the magnetic field lines. In accordance with this, we now make the same assumption as in Cheremnykh et al (2018) and Bahari (2018), namely that the velocity is parallel to the magnetic field, U B. This assumption implies that…”
Section: Problem Formulation and Unperturbed Statementioning
confidence: 97%
“…where 1  and 2  are the densities on both sides of the boundary. The procedure for deriving equality (29) is exactly the same as in the papers by Cheremnykh et al (2018a) and Cheremnykh et al (2018b). In the barometric atmosphere we…”
Section: T T mentioning
confidence: 99%
“…A dispersion relation for the propagation of high-mode (m 2) MHD waves in a magnetized axially moving and rotating twisted jet was derived by Zaqarashvili, Zhelyazkov, and Ofman (2015) and Cheremnykh et al (2018b). That equation was obtained, however, under the assumption that both media (the jet and its environment) are incompressible plasmas.…”
Section: Wave Dispersion Relationmentioning
confidence: 99%
“…In particular, they found that rotation has a stabilizing effect on the current driven mode only for rotation velocities of the order on the Alfvén speed. The more general case, when both the magnetic field and jet flow velocity are twisted, was studied by Zaqarashvili, Zhelyazkov, and Ofman (2015) and Cheremnykh et al (2018b), whose dispersion equations for modes with m 2, represented in different ways, yield practically identical results.…”
Section: Introductionmentioning
confidence: 99%